1996
DOI: 10.1002/j.1460-2075.1996.tb00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the insulin receptor gene in the mouse results in neonatal lethality.

Abstract: Targeted disruption of the insulin receptor gene (Insr) in the mouse was achieved using the homologous recombination approach. Insr+/− mice were normal as shown by glucose tolerance tests. Normal Insr−/− pups were born at expected rates, indicating that Insr can be dispensable for intrauterine development, growth and metabolism. However, they rapidly developed diabetic ketoacidosis accompanied by a marked post‐natal growth retardation (up to 30–40% of littermate size), skeletal muscle hypotrophy and fatty infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
156
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(165 citation statements)
references
References 31 publications
3
156
1
2
Order By: Relevance
“…Somewhat unexpectedly, Joshi et al [7] have reported that skin and pericapsular kidney fat are normally represented in a strain of IR ±/± mice. A major impediment to these experiments is the scarcity of fat tissue in newborn mice, in which it represents approximately 2 % of total body mass, unlike in humans, in whom it represents approximately 16 % [13].…”
mentioning
confidence: 97%
“…Somewhat unexpectedly, Joshi et al [7] have reported that skin and pericapsular kidney fat are normally represented in a strain of IR ±/± mice. A major impediment to these experiments is the scarcity of fat tissue in newborn mice, in which it represents approximately 2 % of total body mass, unlike in humans, in whom it represents approximately 16 % [13].…”
mentioning
confidence: 97%
“…The crucial role of IR in insulin action was confirmed by targeted disruption of the IR gene [2,3]. IRdeficient mice developed severe metabolic disorders soon after suckling, leading to diabetes mellitus, diabetic ketoacidosis (DKA) and liver steatosis, and died within 1 week after birth.…”
mentioning
confidence: 99%
“…Production of mice with targeted disruption of the IR gene has been described [3]. The IR +/-mice were crossed with the L-GK transgenic line to generate IR +/-mice carrying the GK transgene.…”
mentioning
confidence: 99%
“…Insulin knockout mice show no obvious developmental phenotypes but develop diabetes and die within 2 to 3 days of birth [31], while insulin receptor knockout mice are also postnatal lethal [31,32] making it difficult to understand insulin's role in bone metabolism. However, insulin has been suggested to be a bone anabolic agent [33] and does improve the low bone mass phenotype and fracture repair in both T1DM humans and rodents [34].…”
Section: Insulin Treatment In Type 1 Diabetes Mellitus and Bone Fracturementioning
confidence: 99%